AB0227 EXTENSIVE IMMUNOPHENOTYPIC ANALYSIS OF CO-INHIBITORY AND CO-STIMULATORY MOLECULES IN JUVENILE IDIOPATHIC ARTHRITIS (JIA) PERIPHERAL LYMPHOCYTES. (June 2019) - Quesada-Masachs, Estefanía; Sierra, Daniel álvarez de la; Julià, Antonio; Martínez-Gallo, Mónica; Moreno-Cortés, María; Pujol-Borrell, Ricardo; Modesto, Consuelo; Marsal, Sara
Abstract : Background: In a previous in-depth phenotypic analysis of PBLs in JIA, we detected differences in cell subpopulations dependent on the age and also some cellular changes that could be often associated with an exhausted phenotype. Objectives: To analyze the expression of co-inhibitory and co-stimulatory molecules in different cellular subpopulations in Oligoarticular JIA patients stratified by age and treatment. Methods: Exploratory cross-sectional study. 53 patients fulfilling Oligoarticular JIA (ILAR) criteria and 22 controls were included. All of them were children or young adults (2 to 35 years of age). JIA patients were either not treated (n=14) or treated with MTX (n=14), anti-TNF (n=8), or a combination of both (n=16). JIA disease activity was clinically and biologically assessed. Four flow cytometry panels were designed for the analysis of co-stimulatory/co-inhibitory markers, some typical of "exhausted" cells (PD1, TIM 3, TIGIT, CD226, CD137, HVEM, LIGHT, BTLA), assessed in memory, effector and naïve CD4+ and CD8+ T lymphocytes, and also in B lymphocytes and NK cells. Statistical analysis was performed, and FDR correction was applied for p values. Results: No correlation was found among the different exhaustion/activation markers and age neither in JIA nor in controls. Interestingly, age-related differential trends were observed in the CD8+ compartment in controls, while in JIA patients were detected in the B cell compartment. We didn't observe, after correcting for treatment, any significant difference in lymphocyte subpopulations defined by the above co-inhibitory and co-stimulatory markers in JIA patients in relation to indexes of disease activity. However, there was a tendency towards a higher expression of CD137 in several CD8+ subpopulations of active patients as compared to inactive. Conclusion: No clear differences were found in PBL subpopulations of oligoarticular-JIA patients regarding co-stimulatory/co-inhibitory molecules. This finding could be explained, at least in part, by the good therapeutic control achieved in this patient population, or by the particular characteristics of this group of patients, in which prevails a more localized expression of the disease. It could be of interest to carry out complementary analysis to further define the differential tendencies observed. Acknowledgement: Instituto de Salud Carlos III (ISCIII), Sociedad Española Reumatología (SER) Disclosure of Interests: None declared